Exploring Constructivism in Primary School Students' Creativity in Speaking Class - Ni Luh Yunita Purnama Dewi; Dyah Setyowati Ciptaningrum (Ilomata International Journal of Social Science, 2026)
Students’ creativity constitutes a central cognitive–pedagogical capacity that supports speaking skill development within a Constructivism framework, particularly in primary education. Despite its theoretical importance, empirical evidence indicates that the integration of creativity-oriented constructivist strategies in speaking classrooms remains limited, especially in developing contexts. Addressing this gap, this study explores how constructivist pedagogy facilitates students’ creativity in speaking classes. It examines: (1) how constructivist learning models influence creativity, (2) which learning activities are perceived as effective in stimulating creativity, and (3) the challenges faced by teachers in implementation. This qualitative case study involved two English teachers and thirty fifth-grade students, with data collected from six classroom sessions. Data sources included classroom observations, semi-structured interviews, and lesson plan documentation. Students’ creativity was operationalized through indicators of idea fluency, originality, flexibility in language use, and elaboration in speaking performance. Data were analyzed using Thematic Analysis to identify recurring instructional patterns. The findings indicate that constructivist practices enhance students’ creativity through interactive learning, scaffolding, and performance-based assessment. Teachers perceived project-based learning, contextual tasks, and collaborative discussions as effective in fostering creative expression. However, challenges include limited linguistic proficiency, cognitive readiness, and instructional constraints. This study contributes empirically grounded insights into the operationalization of creativity within constructivist speaking instruction at the primary level.